Phospholipid synthesis inside phospholipid membrane vesicles - Sumie Eto; Rumie Matsumura; Yasuhiro Shimane; Mai Fujimi; Samuel Berhanu; Takeshi Kasama; Yutetsu Kuruma (Communications Biology, 2022)
A giant vesicle system combines fatty acid synthesis pathways, CoA recycling, and cell-free acyltransferase gene expression to perform phospholipid synthesis inside.